Modern markers of inflammatory process in surgical practice - A. M. Morozov; A. N. Sergeev; S. V. Zhukov; N. S. Novikova; M. A. Belyak (Амбулаторная хирургия)
Introduction. Currently, one of the important problems in surgery is the search for new markers of the inflammatory process to determine the prognosis of the disease, substantiate the need for surgical intervention and to assess the effectiveness of treatment.Aim. To evaluate the possibilities and prospects of using modern markers of the inflammatory process in the practice of a surgeon.Materials and methods. In the course of the present investigation we analyzed relevant sources of domestic and foreign literature on the topic of application and possibilities of use of modern inflammatory process markers in various fields of medicine. Information was collected from databases of ScienceDirect, Cyberleninka.ru, and PubMed.Results. Acute phase proteins, as markers of inflammation, are valuable tools in the diagnosis, treatment and prognosis of inflammatory diseases, as they are sensitive to systemic inflammation. Important criteria for the use of biomarkers of inflammation are: a low number of false positive results and the possibility of using the marker not only as an indicator of the disease, but also to determine the severity of the patient’s condition. In order to assess the presence of inflammation in clinical conditions, laboratories evaluate the concentrations of various acute phase proteins in plasma. Currently, the most relevant markers of inflammatory processes are: C-reactive protein; haptoglobin; presepsin is also an early indicator of inflammation; fibrinogen; serum amyloid A; a complement system containing key markers of inflammation. Determining them in the surgeon’s practice will allow you to predict the outcome of the disease and evaluate the results of treatment.Conclusion. At the moment, the determination of inflammatory markers helps in predicting the disease, planning treatment tactics, evaluating the effectiveness of therapy after surgery and in earlier diagnosis of severe conditions.